P773 Rescue treatment with tacrolimus in patients with severe inflammatory bowel disease (IBD) without response to intensification of biological therapy. (16th January 2018) - Sanchis, L; Cortés, X; Clofent, J; Rodriguez, J; Molés, J R; Fernández, S; Borrás, J
Abstract: Background: A significant percentage of patients with IBD do not respond to biological treatment. Tacrolimus (TAC) has shown utility in Crohn's disease (CD) and severe ulcerative colitis (UC) refractory to anti-TNFα. There are no published data on combination of biological therapy and TAC in IBD. We therefore investigated the efficacy and safety of combination intensified biological treatment (IBT) and TAC in severe IBD refractory to IBT alone. Methods: Observational, prospective study of patients with IBD in Hospital de Sagunto, Spain, from 2012 to the present. Inclusion criteria are adult patients with moderate-to-severe IBD without clinical response to IBT 12 weeks after initiation were included. We introduced TAC therapy (0.2 mg/kg/day) in these patients. Blood TAC levels were performed at week 2, 4, 8 and every two months thereafter. The response was measured according to the Harvey Index for CD and Mayo Index for UC. Biological response was considered as ≥50% decrease in CRP and fecal calprotectin and biological remission was considered as normalisation of these values. Results: Fourteen patients (three women) were included. Six UC (two with UC left and four with pancolitis) and eight CD (three L2; five L3; four B1; three B2; four p). Average age was 42 years. Average of years of IBD evolution was 12.4. 42.8% of the patients were corticodependents and 21.4% were refractory patients. 78.6% of the patients were in cotreatment with immunosuppressant (thiopurine/methotrexate). Only six patients (all with infliximab) had received a single biological, eight received ≥2 biologicals. Of the 14 patients included, 6 received IFX, four Adalimumab, three Vedolizumab, and one ustekinumab. All patients were intensified according to usual clinical practice. In all patients, thiopurine or methotrexate was withdrawn prior to the introduction of TAC. In 100% of patients, the previous endoscopy showed moderate–severe activity. Average time of TAC treatment was 7.8 months (1–18). Nowadays, seven patients continued on combination therapy. Clinical response and remission during follow-up were achieved in 64% of UC patients and 43% of CD patients. In four of six corticoid-dependents patients, corticosteroids withdrawal was achieved. Almost half of the patients presented biological remission and 36% did not respond biologically. TAC blood levels out of range were presented in 8 patients. During combination therapy, these adverse effects were recorded: tremor (5), abdominal pain (2), hypertension (1), renal (1), insomnia (1). Three patients had to suspend due to bad tolerance of TAC therapy. Any serious adverse events were developed. Conclusions: Almost half of patients with severe IBD and no response to intensified biological therapy achieve clinical remission with the combination of TAC, without any serious adverse events.